Danger control and fear control during public health emergencies: Considering the roles of fear and hope in the EPPM across different levels of trust. Issue 5 (24th June 2022) - Chen, Liang; Chen, Minyi
Abstract: Public health emergencies pose considerable threats to global health and safety. The control of these emergencies requires the efforts of healthcare professionals and calls for the public to take protective actions. The present study not only puts fear back in the extended parallel process model (EPPM) but also considers another similarly productive emotion: hope. We examined the mechanisms behind the effects of four cognitive perceptions on protective actions (i.e., danger control) and information avoidance (i.e., fear control). A national online survey was conducted with 1676 participants during the outbreak of COVID‐19 in China from February 1 to 29, 2020. The results revealed that perceived severity and susceptibility could lead to fear, positively affecting protective actions. On the other hand, perceived response efficacy and self‐efficacy induced hope, which was positively associated with protective actions but negatively associated with information avoidance. Furthermore, the mechanisms behind the relationships among cognitions, emotions, and behaviors varied across levels of trust in healthcare systems.